118k views
2 votes
Simplify the expression:
(8+-9)(9+-8)

User Cccn
by
5.7k points

2 Answers

2 votes

Answer:


-1

Explanation:


[8 + −9][9 + −8] = [8 - 9][9 - 8] = [1][-1] = -1

I am joyous to assist you anytime.

User Cira
by
6.0k points
6 votes

Answer:

-1

Explanation:

(8 + -9)(9 + -8)

A negative times a positive is a negative.

8 + -9

+- = -

8 - 9

8 - 9 = -1

(-1)(9 + -8)

9 + -8

+- = -

9 - 8

9 - 8 = 1

(-1)(1)

Now, we multiply

Remember, a negative times a positive equals a negative.

-1 * 1 = -1

Our answer is -1

User Asperi
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.